Explaining the needs of family caregivers of patients undergoing gynecological surgery for physical facilities and equipment in hospital - Nasrin Galehdar; Marzieh Hasanpour; Ashraf Kazemi (Tehran University of Medical Sciences, 2021)
Background & Aim: Designing healthcare spaces and physical facilities requires the identification of the patientchr('39')s family needs, and it is considered an important component of nursing theories. The aim of this study was to explain the needs of family caregivers of patients undergoing gynecological surgery for physical facilities and equipment in hospital. Methods & Materials: This study is based on the results of the qualitative part of a large hybrid study on the development and implementation of a need-based service delivery program for the caregivers of patients undergoing gynecological surgery in 2017. The selection of participants was purposefully done with maximum variation. The study data were collected using 31 (16 caregivers, 6 nurses, 4 doctors, 3 patients and 2 service workers) in-depth interviews and observations and analyzed by the conventional qualitative content analysis using the Zhang and Wildemuth approach. Results: Data analysis led to the development of the theme "need for physical facilities", which fell into two categories "need for proper physical structure in the hospital" with the following subcategories: "need for care facilities behind the operating room door", "need to provide welfare facilities in the hospital for caregivers", "need for welfare facilities in the surgical ward", "necessity of allocating rooms to the similar patients", and category "need for appropriate hospital facilities and equipment" with subcategories "caregiver's need for facilities and amenities", and "caregiver's need for facilities and amenities for the comfort of the patient". Conclusion: The results show the importance of having a physical structure tailored to the needs of family caregivers as well as the availability of appropriate facilities and equipment in hospital. One of the limitations of the study was preventing men from visiting patients in the women's hospital. It is recommended that the needs of male companions and the necessity of their presence according to the cultural context be studied. Also, a new architectural design is suggested to create a suitable therapeutic environment and positive effect on patients' improvement and increase patient and family satisfaction.